Skill transferability, regret and mobility - Lex Borghans; Bart H. H. Golsteyn (Institute for the Study of Labor (IZA), 2006)
After graduation many students start working in sectors not related to their field of study or participate in training targeted at work in other sectors. In this paper, we look at mobility immediately after graduation from the perspective that educational choices have been made when these pupils had little experience of the actual working life in these professions. We develop a model where students accumulate partially transferable human capital but also learn about their professional preferences at the university and during the first years in the labor market. As a consequence of this newly acquired insight, these young workers might realize that working in another occupational field would better fit their preferences, although they are better equipped to work in their own field. The empirical analysis reveals that if wages are 1% lower due to lower skill transferability, the probability that a graduate who regrets his choice actually switches decreases by 2.2 percentage points, while those who switch on average take 0.3 months additional education.
Keywords: J24; J44; J62; 330; regret; mobility; skill transfer; training; Berufseinstieg; Arbeitsmobilität; Anforderungsprofil; Qualifikation; Niederlande